Genetic variability in crosses of aromatic and non-aromatic rice (oryza sativa L.) For morphophysicochemical, quality, and yield trait improvement / Nur Suraya Abdullah - Abdullah, Nur Suraya (2024)
The research was carried out among seven parental lines, viz., Malaysian rice varieties (MRQ50, MRQ74, MRQ76, MR219, Mahsuri Mutant, Mahsuri Mutant 98), and Indian traditional rice (Basmati 370), including eleven F1 hybrids. The main objective was to develop superior rice breeding lines with enhanced morphophysicochemical, quality, and yield traits. Eleven rice hybrids were developed through the hybridization technique, and the seeds harvested were then planted on a field plot to assess their performance and heterosis value. The selected cross was then advanced until the F4 generation by the single seed descent technique to speed up the breeding cycle. The F5 and F6 plants were then spaced and planted in the field plot for the selection of desired traits. The data comprised mean performances, genetic parameters, heterosis, and genetic analysis. The findings revealed that a hybrid developed from a cross between the Basmati 370 and MR 219 rice varieties has demonstrated high performances in most of the yield-contributing traits, such as length of panicle, number of fertile panicles, number of tillers, length of flag leaf, and thousand-grain weight. The hybrid also has a long grain (> 6.0 mm) and demonstrated the longest grain length of cooked rice, about 12.45 mm, as compared to other crosses. The value of the phenotypic coefficient of variation was also higher than the genotypic coefficient of variation, but with a low magnitude, which indicated the influence of environmental factors on the traits. About 196 rice genotypes, including parents and five check varieties, were raised in the field plot. Data was recorded and analysed, and the rice genotypes were divided into five main clusters by various traits. The finding showed that Clusters 1 and III comprised 91 and 42 genotypes, respectively, and were categorised as tall plants. Basmati 370 was classified under Cluster III, which has long flag leaves and the highest thousand-grain weight, while MR219 was classified under Cluster IV. Cluster IV, which comprised 36 genotypes, was suitable for the selection of genotypes with intermediate height and moderate panicle length and grain length. The results indicated that inbred lines that showed widely divergent clusters could be used in hybrid breeding programs. The knowledge and information gathered from this study can serve as a basis for future rice quality improvement programmes.